Miscellanea Zoologica. The British Nereides (2). [Continued from vol. iii p. 295]. - Johnston, George (Annals of Natural History or Magazine of Zoology, Botany and Geology, Series 1, 1840)
[None]
World Polychaeta Database (WPolyD)